Systematic Literature Review: The Effect of Generative Artificial Intelligence on Students' Critical Thinking Abilities in Science Learning - Dina Fajrin (EDUJAVARE: International Journal of Educational Research, 2026)
The proliferation of Generative Artificial Intelligence (GenAI) tools in education has prompted urgent questions about their impact on higher-order cognitive skills. In science education, where critical thinking and scientific reasoning are foundational, understanding how GenAI reshapes these competencies is essential. This study employs a Systematic Literature Review (SLR) following PRISMA 2020 guidelines to synthesize empirical evidence on the effects of GenAI on students' critical thinking skills in science learning contexts. A comprehensive search across Scopus, ERIC, and Google Scholar databases spanning 2020-2026 identified 25 eligible studies. Findings reveal a conditional dual impact: GenAI enhances critical thinking when integrated within structured inquiry and problem-based frameworks, but poses risks of cognitive over-reliance and surface-level processing when used without pedagogical scaffolding. Critical moderating factors include AI literacy, instructional design quality, teacher facilitation, and task structure. The novelty of this review lies in its exclusive focus on the intersection of GenAI, critical thinking, and science education. Implications for curriculum designers, science teachers, and policymakers in developing-country contexts are discussed